Epidemiological Analysis of Zika Virus and Its Complications in Pregnant Women, Peru 2016–2023 - Mateo, Susan Y. (2025)
Introduction: Zika is an emerging arboviral disease that entered Peru in 2016, associated with congenital malformations and neurological complications. Objective: To analyze the incidence and distribution of Zika and identify complications in pregnant women in Peru during the 2016–2023 period. Materials and methods: Observational, descriptive study based on secondary data from the national epidemiological surveillance system. Annual incidence rates (AIR) and average annual incidence rates (AAIR) were calculated by age group, sex, and geographic region. Results: A total of 4529 confirmed cases were reported (national AAIR: 2.62 per 100,000 population), with an epidemic peak in 2019 (AIR: 11.03 per 100,000). Focal outbreaks were identified in 12 departments, with the highest burden in Cajamarca (AAIR: 17.42) and Loreto (AAIR: 11.59). The highest AAIR was observed among young adults (2.04), females (2.19), and women of reproductive age (2.94). No confirmed cases of Zika-related microcephaly were reported. Conclusions: Zika transmission in Peru occurred through focal outbreaks, with lower magnitude compared to other countries in the region. No cases of microcephaly attributable to the virus were confirmed. Findings highlight the need to strengthen integrated arbovirus surveillance and enhance prevention and control measures.